ALASAN BERHENTI MEROKOK PADA WANITA MANTAN PECANTU ROKOK DI KOTA MADIUN - Any Setyawati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2017)
Smokers in Indonesia increased in the age group above 15 years, namely 34.2 percent (2007), 34.7 percent (2010), and the latest data reached 36.3 percent (2013). The data shows if the proportion of female smokers reached the highest figure of 4.7% in Papua. Head of Madiun City Health Office drg. Widwiono asserted, the determination of the area without smoking is done because in the city the number of active smokers is quite high. Results of the Clean and Healthy Lifestyle survey (PHBS) show, of the 1,200 houses surveyed, 646 homes are among active smokers. This shows half more, 53.86% of the surveyed smokers. This study aims to determine the factors that affect the process of quitting smoking in women former cigarette addicts. This research method is qualitative research, with approach of Grounded theory. Data collection was done to 10 female respondents of former cigarette addicts with in-depth interview method. Data analysis & coding used in this research is triangulation of data that is done continuously until the data obtained saturated. The results show that the process of quitting smoking can successfully require a support from within yourself and from outside. Intentions that arise in themselves are greater than the support provided by family and peers. Based on these results it is concluded that for a woman smoker, to stop her smoking habit there must be a strong reason arising from within oneself without any coercion from anywhere. Key word : Ex- addict, Smoke, Woman